Social Anxiety and Close Relationships: A Hermeneutic Phenomenological Study - Nielsen, Kate E. J.; Cairns, Sharon l. (Canadian Journal of Counselling and Psychotherapy, 2009)
Few studies have looked at social anxiety and close relationships. Whereas these studies were quantitative, this study used the qualitative approach of hermeneutic phenomenology to explore the meaning of being in a close relationship for 8 individuals with social anxiety. Participants completed a written questionnaire with open-ended questions about their experiences in their closest relationship. The themes suggest that these individuals are capable of forming close relationships, but that they tend to adopt an insecure attachment style in their relationships. The themes are discussed in light of cognitive behavioural and interpersonal theory and therapy.